Pengembangan Aplikasi Perpustakaan Digital dengan Metode Pembayaran Otomatis API Dompet Digital Berbasis Mobile - Wahyu Zebua; Jamaluddin Jamaluddin; Eva Julia G. Harianja (Universitas Methodist Indonesia, 2024)
Technological advancements have changed the landscape of payment apps significantly. This paper presents an analysis of how continuously evolving technology has enabled payment applications to provide more efficient and convenient solutions for users. Payment applications can not only be used in buying and selling transactions but can be applied in various applications such as digital libraries which are an important means of supporting information access and digital literacy. However, there are still many digital libraries that do not utilize automatic payment methods to increase user efficiency and convenience. This development aims to develop a digital library application with the integration of automatic payment methods to improve user experience and library management efficiency. The research results show that the integration of automatic payment methods in digital library applications can increase efficiency in the payment process. The practical implication of this research is to provide recommendations for digital library application developers to utilize automatic payment technology to improve the quality of library services and management.